Financing agricultural R&D in rich countries: what's happening and why - Alston, Julian M.; Pardey, Philip G.; Smith, Vincent H. (Wiley, 1998)
Governments everywhere are trimming their support for agricultural R&D, giving greater scrutiny to the support that they do provide, and reforming the public agencies that fund, oversee, and carry out the research. This represents a break from previous patterns, which had consisted of expansion in the public funds for agricultural R&D. Private‐sector spending on agricultural research has slowed along with the growth of public spending in recent years, but the balance continues to shift towards the private sector. This article presents a quantitative review of these funding trends and the considerable institutional changes that have accompanied them. We discuss new data for 22 OECD countries, providing institutional details for five of these countries, and conclude with an assessment of policy developments.